ANALYSIS OF THE USE OF DIGITAL MARKETING AND PRODUCT INNOVATION ON MARKETING PERFORMANCE OF FURNITURE SMEs IN GONDANGSARI VILLAGE, JUWIRING DISTRICT, KLATEN - Mahendra, Vidorova Ardian; Hartono, Sri; Marwati, Fithri Setya; Kustiyah, Eny; Istiqomah, Istiqomah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The advantages of digital marketing for businesses and MSMEs include the ability to easily connect with consumers online, higher sales conversions for targeted consumers, more efficient marketing costs, the ability to serve consumers in real time, and the potential to increase MSMEs' selling power. Furthermore, one of the important aspects that SMEs must carry out in order for the business in which they are involved to develop properly is to innovate. The goal is that the types of products and services offered are different from those of competitors, so that consumers will come. The purposes of this study were (1) to determine the effect of the use of digital marketing on marketing performance in MSMEs Furniture in Gondangsari Village, Juwiring District, Klaten Regency and (2) to determine the effect of product innovation on marketing performance in MSMEs Furniture in Gondangsari Village, Juwiring District, Klaten Regency. The analytical approach used in this research is descriptive quantitative. The population in this study is 38 people. The sample in this study were 38 people. According to the findings, the t test (Partial Test) has a significant value for the variable use of digital marketing, namely 0.002 < 0.05, implying that the variable use of digital marketing has a significant effect on marketing performance at MSMEs Furniture in Gondangsari Village, Juwiring District, Klaten Regency. According to the t test (Partial Test) results, the significant value for the product innovation variable is 0.006 < 0.05, implying that the product innovation variable has a significant effect on marketing performance in MSMEs Furniture in Gondangsari Village, Juwiring District, Klaten Regency.Keywords: Use of Digital Marketing, Product Innovation, Marketing Performance, MSMEs Furniture.